Diversifying the use of tuna to improve food security and public health in Pacific Island countries and territories. (January 2015) - Bell, Johann D.; Allain, Valerie; Allison, Edward H.; Andréfouët, Serge; Andrew, Neil L.; Batty, Michael J.; Blanc, Michel; Dambacher, Jeffrey M.; Hampton, John; Hanich, Quentin; Harley, Shelton; Lorrain, Anne; et al.
Abstract: The large tuna resources of the Western and Central Pacific Ocean are delivering great economic benefits to Pacific Island countries and territories (PICTs) through sale of licences to distant water fishing nations and employment in fish processing. However, tuna needs to contribute to Pacific Island societies in another important way—by increasing local access to the fish required for good nutrition to help combat the world's highest levels of diabetes and obesity. Analyses reported here demonstrate that coastal fisheries in 16 of the 22 PICTs will not provide the fish recommended for good nutrition of growing Pacific Island populations, and that by 2020 tuna will need to supply 12% of the fish required by PICTs for food security, increasing to 25% by 2035. In relative terms, the percentages of the region's tuna catch that will be needed in 2020 and 2035 to fill the gap in domestic fish supply are small, i.e., 2.1% and 5.9% of the average present-day industrial catch, respectively. Interventions based on expanding the use of nearshore fish aggregating devices (FADs) to assist small-scale fishers catch tuna, distributing small tuna and bycatch offloaded by industrial fleets at regional ports, and improving access to canned tuna for inland populations, promise to increase access to fish for sustaining the health of the region's growing populations. The actions, research and policies required to implement these interventions effectively, and the investments needed to maintain the stocks underpinning the considerable socio-economic benefits that flow from tuna, are described. Highlights: There is a shortfall in coastal fish available for food security in the Pacific Islands. Greater fish consumption is needed to combat prevalent non-communicable diseases. Tuna will need to supply 12% of fish required by the Pacific in 2020 and 25% by 2035. These quantities of tuna are 2.1% and 5.9% of the present-day catch, respectively. Policies are needed to provide communities with access to tuna allocated for food.